Tacrolimus, a calcineurin inhibitor, promotes capsaicin-induced colonic pain in mice - Kazuki Matsui; Yuka Terada; Maho Tsubota; Fumiko Sekiguchi; Atsufumi Kawabata (Elsevier, 2020)
TRPV1 is phosphorylated and functionally upregulated by protein kinases, and negatively regulated by phosphatases including calcineurin. Since the clinical use of calcineurin-inhibiting immunosuppressants is commonly associated with chronic diarrhea, we examined if tacrolimus, a calcineurin inhibitor, promotes TRPV1-dependent colonic hypersensitivity in mice. Intracolonic administration of capsaicin, a TRPV1 agonist, caused referred hyperalgesia in the lower abdomen, an effect prevented by capsazepine, a TRPV1 blocker. Tacrolimus accelerated the intracolonic capsaicin-induced referred hyperalgesia. Similarly, intracolonic capsaicin caused spinal ERK phosphorylation, a marker for nociceptor excitation, an effect promoted by tacrolimus. Thus, tacrolimus may aggravate TRPV1-related colonic pain accompanying irritable bowel syndrome. Keywords: Tacrolimus, Colonic pain, TRPV1